Cultural Origin of European Modern Design - Wang, Zhiyong (Journal of Visual Art and Design, 2024)
Cultural studies of modern design are of great importance to scholarly research of modern design history, particularly in the context of the trend towards analysis and interpretation of modern design from sociological and cultural points of view. This article investigates the link between European modern design and the tradition of Western culture. Based on the definition of rationalism and idealism as ideal types of the Western cultural tradition, the investigation revealed that European modern design presents these ideal types through diversified design activities in the modern movements. It concludes that European modern design, as visualization of cultural codes, is a manifestation of Europe’s cultural heritage, although it reflects a revolutionary stance against the cultural background of modernization and achieved a breakthrough that showed the innovative quality of modern culture. This study also unfolded the long-term effect of culture on the rise of European modern design, which strongly indicates culture’s continuity in the long-range historical process and explains that the significance of European modern design is embodied not only in the revolution or innovation of modern culture but also in cultural inheritance and historical continuity.